Analysis of annual changes in freight turnover of road transport using time series model (Международный научный журнал «Инженер», 2026)
This article presents a statistical analysis of the volume of freight turnover in automobile transport forthe period 2010–2023. The analysis was performed using Minitab 17 software, with linear and quadratictrend models constructed and their accuracies compared. Additionally, the autocorrelation of modelresiduals was examined, and a forecast of freight turnover volume for 2024–2026 was made. The resultsindicate an increasing annual growth trend in freight volume. These results are of great importance forthe development of transport infrastructure, the improvement of logistics systems, and the identificationof investment directions. During the analysis, the time dynamics of the variables were thoroughly studied,and statistically grounded conclusions were drawn. The findings enabled the formulation of practicalrecommendations that can be applied in economic forecasting.